Der Fundplatz von Mang de Bargen – Ein bronzezeitliches Gräberfeld in Schleswig-Holstein - Schaefer-Di Maida, Stefanie (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
The Mang de Bargen site near Bornhöved (district of Segeberg), once the target of gravel works, developed into one of the best-dated Bronze Age sites in Schleswig-Holstein. The burial ground was used from the Late Neolithic to the Pre-Roman Iron Age for burying the dead. For this long period of use, several cultural changes, including burial rites, furnishings and further activities can be traced. The consistent dating of almost all the graves allows in particular concretising the change from inhumation to cremation and the transition from burial mounds with tree coffins to the beginning of the use of urns in northern Germany. Anthropological analyses of the cremations from Mang de Bargen and other sites in the area also reveal the age-related placement and furnishings, which motivate new discussions. The aim of this contribution is to present and discuss the latest results from the site and the surrounding area.